The burden, risk factors, causative pathogens, and outcome of bloodstream infections in hematopoietic stem cell transplant recipients; single center experience from Pakistan - Rezwan, Faiza; Samad, Shafaq Abdul; Fatima, Mushkbar; Sharif, Zainab; Jamal, Aisha; Zaidi, Uzma (Infectious Diseases Journal of Pakistan, 2025)
Background: Hematopoietic stem cell transplant (HSCT) is an effective therapeutic option for various metabolic, immunologic, and hematologic disorders and has shown promising results in patients with various hematological malignancies over the years. However, bloodstream infections (BSI) are still one of the leading causes of morbidity and mortality in patients undergoing HSCT. The objective of this study is to evaluate the causative pathogen, risk factors, and outcome of bloodstream infections in HSCT patients. Material and Methods: A retrospective cohort analysis from January 2019 to July 2021 was carried out on 116 patients who underwent HSCT at the National Institute of Blood Disease and Bone Marrow Transplantation. Results: Among the 116 patients, 63.8% (n=74) were males and 38.2% (n=42) were females. The median age of the patients was 11 years (range, 0.7 to 62; IQR, 4.7 to 21 years). The incidence of bloodstream infections (BSI) was 37.9% (n=44) at 30 days, 25.0% (n=29) at 60 days, and 19.8% (n=23) at 90 days. A total of one hundred and fifty-five pathogens were detected in 116 patients; among which 103 (66.5%) were Gram-negative and 52 (33.5%) were Gram-positive organisms. Out of the 116 patients, 89.7% (n=104) were successfully treated and the overall mortality rate was 10.3% (n=12) in this study. Conclusion: Gram-negative bacteria were the most frequently occurring pathogens in BSIs, followed by Gram-positive bacteria. The mortality associated with BSIs can be substantially reduced with the judicious use of empirical antibiotics and the implementation of appropriate infection control measures in transplant care. Keywords: Hematopoietic stem cell transplant, bloodstream infections, Gram-positive and Gram-Negative organism, immunosuppression